2018
DOI: 10.1111/jcmm.13464
|View full text |Cite|
|
Sign up to set email alerts
|

H3 relaxin inhibits the collagen synthesis via ROS‐ and P2X7R‐mediated NLRP3 inflammasome activation in cardiac fibroblasts under high glucose

Abstract: Excessive production of reactive oxygen species (ROS) and P2X7R activation induced by high glucose increases NLRP3 inflammasome activation, which contributes to the pathogenesis of diabetic cardiomyopathy. Although H3 relaxin has been shown to inhibit cardiac fibrosis induced by isoproterenol, the mechanism has not been well studied. Here, we demonstrated that high glucose (HG) induced the collagen synthesis by activation of the NLRP3 inflammasome, leading to caspase‐1 activation, interleukin‐1β (IL‐1β) and IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
56
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 29 publications
2
56
1
1
Order By: Relevance
“…Inhibiting TXNIP can effectively down‐regulate NLRP3 inflammasome activation and IL‐1β secretion . Moreover, one study has recently shown that ROS can directly induce the formation of the caspase‐1‐ASC complex and activate the NLRP3 inflammasome . In the current study, we found that ROS could induce cytochrome c influx into cytoplasm, which directly bound to NLRP3 and led to NLRP3 inflammasome activation.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Inhibiting TXNIP can effectively down‐regulate NLRP3 inflammasome activation and IL‐1β secretion . Moreover, one study has recently shown that ROS can directly induce the formation of the caspase‐1‐ASC complex and activate the NLRP3 inflammasome . In the current study, we found that ROS could induce cytochrome c influx into cytoplasm, which directly bound to NLRP3 and led to NLRP3 inflammasome activation.…”
Section: Discussionsupporting
confidence: 49%
“…Recent studies suggest that mitochondrial ROS is required for NLRP3 inflammasome activation . Moreover, many studies have indicated that mitochondrial damage and oxidative stress are important risk factors for DCM and that mitochondrial ROS is a pivotal link between oxidative stress and NLRP3 inflammasome activation . Recently, a study has shown that monocytes and/or MDMs from T2D or DCM patients stimulated with DAMP release an elevated level of ROS .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is considerable in vitro and in vivo evidence that relaxin is an important factor in the progression and treatment of fibrosis. In addition, there is emerging evidence that additional relaxin family peptides, such as relaxin-3, may also play a role in fibrosis (Hossain et al, 2011;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cl.casp‐1 leads to mature IL‐1β and IL‐18 release, which triggers inflammation. In diabetes‐related studies, streptozocin injection increases NLRP3‐induced inflammation; however, NLRP3 inhibition ameliorates cardiac dysfunction in a model of DCM (Luo et al, ; Ye, Bajaj, Yang, Perez‐Polo, & Birnbaum, ; X. Zhang et al, ). All the above studies demonstrated that inhibition of cardiac fibrosis and inflammation at the same time may be a promising therapeutic strategy for DCM.…”
Section: Introductionmentioning
confidence: 99%